Effect of carob variety and roasting on the antioxidant capacity, and the phenolic and furanic contents of carob liquors - Rodríguez-Solana, Raquel; Salgado, José M.; Peréz-Santín, Efren; Romano, Anabela (Journal of the Science of Food and Agriculture, 2019)
BACKGROUND The production of the traditional carob liquor from Algarve (Portugal) depends on numerous factors such as carob processing, variety and maceration conditions. An experimental design with 36 runs was created to evaluate the effect of the roasting temperature, particle size, variety of carob and time of maceration on several parameters of carob liquors as gallic acid and total phenolic content, the furanic composition (furfural and 5-(hydroxymethyl)furfural), browning index and in vitro antioxidant capacity. RESULTS The results revealed that carob variety was the independent variable with the greatest effect on antioxidant capacity, total phenolic and gallic acid content. In particular, AIDA liquors presented the highest results, mainly those prepared with unroasted carob. Meanwhile, Galhosa and Mulata liquors showed the greatest concentrations when the carob pulp was roasted at 150 degrees C. The furanic composition and browning index were greatly influenced by the carob roasting degree. CONCLUSION The levels of the main toxic furanics present in carob liquors, furfural and 5-(hydroxymethyl)furfural, suggest a safe consumption of these beverages even in samples of carobs with the maximum roasting degree. The smallest carob particle size favoured the highest phenolic extraction, while the longest maceration periods decreased the concentration of the toxic furanic compounds studied.
Keywords: ceratonia siliqua L; maceration; roasting; phenolic compounds; furanic compounds; JCR; Scopus